2008
DOI: 10.1111/j.1742-7843.2008.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Inhibition of CYP3A4 Metabolism and P‐Glycoprotein‐Mediated Transport by Trade Herbal Products

Abstract: Extracts of six commonly used commercially available herbal products, St. John's wort, common valerian, common sage, Ginkgo biloba , Echinacea purpurea and horse chestnut were investigated for their in vitro inhibitory potential of CYP3A4 mediated metabolism and P-glycoprotein efflux transport activity. C-DNA baculovirus expressed CYP3A4 and Caco-2 cells were used. Ketoconazole and verapamil were applied as positive control inhibitors, respectively. A validated high-performance liquid chromatography methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 65 publications
7
68
1
Order By: Relevance
“…Pharmacokinetic changes of cilostazol may be possible with the co-administration of the CYP inhibitor because it is metabolized mainly via CYP. There are some reports that G. biloba extract inhibited in vitro CYP 3A mediated metabolism (Zou et al, 2002;Hellum and Nilsen, 2008). The results from the present study (Table I) indicated that G. biloba extract mildly inhibits CYP2C8, CYP2C9, and CYP2C19 activities with IC50 of 30.8, 60.5, and 25.2 μg/ml, respectively, in human liver microsomes.…”
Section: Discussionmentioning
confidence: 51%
“…Pharmacokinetic changes of cilostazol may be possible with the co-administration of the CYP inhibitor because it is metabolized mainly via CYP. There are some reports that G. biloba extract inhibited in vitro CYP 3A mediated metabolism (Zou et al, 2002;Hellum and Nilsen, 2008). The results from the present study (Table I) indicated that G. biloba extract mildly inhibits CYP2C8, CYP2C9, and CYP2C19 activities with IC50 of 30.8, 60.5, and 25.2 μg/ml, respectively, in human liver microsomes.…”
Section: Discussionmentioning
confidence: 51%
“…During the past decade, several potential mechanisms of interactions of valerian preparations, involving CYP enzymes, P-glycoprotein, and UGTs, have been studied in vitro [36,[38][39][40][41][42]46]. Some of these studies pointed to a possible drug interaction potential by valerian extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, the same preparation was used, and an IC 50 for CYP 3A4 inhibition at a concentration of 0.756 mg/mL was observed [40]. Slight but significant effects on bidirectional digoxin transport (involving P-gp) were found only with 1.875 mg/mL.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In an in vitro study in Caco-2 cells, it was demonstrated that the inhibitory effect of various Echinaceae extracts on CYP3A4 and P-gps showed large variability depending on the total alkamide content of the extract (101). Gorski et al (2004) studied the effect of Echinaceae on various CYP enzymes in healthy human volunteers using different probe drugs, namely caffein (CYP1A2), tolbutamide (CYP2C9), dextromethorphan (CYP 2D6) and midazolam (CYP3A4), and observed that it significantly reduces the clearence of only caffein (CYP1A2) and tolbutamide (CYP2C9).…”
Section: Echinaceaementioning
confidence: 99%